Design of Qur'an Tahfidz Programme at Al-Azhar 48 Islamic Junior High School (SMP) Samarinda - Hamzah, Muchamad RIfai; Setiawan, Agus (Pascasarjana IAIN Kudus, 2024)
This paper aims to analyse the design of the Quran memorising program used in Al-Azhar 48 Islamic Junior High School (SMP) in Samarinda. This research method uses descriptive qualitative. The data collection technique was carried out by means of observation, interviews and documentation. Then the data analysis technique uses data triangulation as a form of synchronisation. The results of this study can be concluded that the tahfidz programme design used is: a) The planning stage which includes determining the person in charge, determining the objectives, determining the time allocation and schedule. b) The implementation stage consists of diagnostic assessment, halaqoh formation, memorising, memorising murajaah and tahsin matriculation. c) The evaluation stage is evaluation through a religious monitoring book, internal evaluation and at the end an external evaluation is carried out.